Early development of local data dashboards to depict the substance use care cascade for youth involved in the legal system: qualitative findings from end users - Allyson L. Dir; Lauren O'Reilly; Casey Pederson; Katherine Schwartz; Steven A. Brown; Khairi Reda; Logan Gillenwater; Sami Gharbi; Sarah E. Wiehe; Zachary W. Adams; Leslie A. Hulvershorn; Tamika C.B. Zapolski; et al. (BMC, 2024)
Abstract Introduction Rates of substance use are high among youth involved in the legal system (YILS); however, YILS are less likely to initiate and complete substance use treatment compared to their non legally-involved peers. There are multiple steps involved in connecting youth to needed services, from screening and referral within the juvenile legal system to treatment initiation and completion within the behavioral health system. Understanding potential gaps in the care continuum requires data and decision-making from these two systems. The current study reports on the development of data dashboards that integrate these systems' data to help guide decisions to improve substance use screening and treatment for YILS, focusing on end-user feedback regarding dashboard utility. Methods Three focus groups were conducted with n = 21 end-users from juvenile legal systems and community mental health centers in front-line positions and in decision-making roles across 8 counties to gather feedback on an early version of the data dashboards; dashboards were then modified based on feedback. Results Qualitative analysis revealed topics related to (1) important aesthetic features of the dashboard, (2) user features such as filtering options and benchmarking to compare local data with other counties, and (3) the centrality of consistent terminology for data dashboard elements. Results also revealed the use of dashboards to facilitate collaboration between legal and behavioral health systems. Conclusions Feedback from end-users highlight important design elements and dashboard utility as well as the challenges of working with cross-system and cross-jurisdiction data.